1997
DOI: 10.1177/1046496497284003
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Collective Efficacy and Performance in Manufacturing Work Teams

Abstract: This study explores the construct of collective efficacy for self-managed work teams in a manufacturing setting. The construct is developedfrom a historical perspective through the team literature and the self-efficacy literature. Collective efficacy and performance behaviors are measured at four time periods for eight work teams. A positive relationship was discovered using repeated measures analysis of variance, indicating that higher efficacy is related to higher levels of performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 15 publications
2
73
0
1
Order By: Relevance
“…This positive association was found across a broad range of participants, experimental designs, and measurement approaches. Furthermore, at the level of the group, scholars have shown that groups with high collective efficacy are more likely to persist than groups with low collective efficacy (e.g., Hodges and Carron 1992;Little and Madigan 1997). Entrepreneurs working in settings where collective efficacy (e.g., of the entrepreneurial team) is high are therefore likely to be more motivated to persist with their venture than those working in settings with low collective efficacy.…”
Section: Perceived Collective Efficacymentioning
confidence: 99%
“…This positive association was found across a broad range of participants, experimental designs, and measurement approaches. Furthermore, at the level of the group, scholars have shown that groups with high collective efficacy are more likely to persist than groups with low collective efficacy (e.g., Hodges and Carron 1992;Little and Madigan 1997). Entrepreneurs working in settings where collective efficacy (e.g., of the entrepreneurial team) is high are therefore likely to be more motivated to persist with their venture than those working in settings with low collective efficacy.…”
Section: Perceived Collective Efficacymentioning
confidence: 99%
“…Theorists contend that efficacy beliefs are a primary determinant of human behavior. Efficacy expectations are hypothesized to influence behavior through three primary mechanisms-cognitive, motivational, and affective (Little & Madigan, 1997). Personal efficacy influences people's "success/failure imagery, worry, goal setting, and attributions" (George & Feltz, 1995).…”
Section: Self-efficacymentioning
confidence: 99%
“…Personal efficacy influences people's "success/failure imagery, worry, goal setting, and attributions" (George & Feltz, 1995). For example, efficacious individuals are more likely to visualize future success which often leads to increased concentration and effort during actual performance (Little & Madigan, 1997). Efficacious individuals are also more likely to attribute success to a dispositional cause rather than a situational factor.…”
Section: Self-efficacymentioning
confidence: 99%
See 2 more Smart Citations